DENTAL IMPLANTS TO RESTORE PATIENT'S QUALITY OF LIFE - Yunita Viryadi, Mieke; Tjandrawinata, Rosalina (Journal of Health and Dental Sciences, 2025)
Tooth loss can lead to physical and psychological problems such as impaired chewing, digestive disorders, changes in facial structure, speech difficulties, and reduced self-confidence, which may trigger anxiety and depression. The 2023 Indonesian Health Survey reported that although 31.9% of people had experienced tooth extraction, only 3.1% had their teeth replaced, showing a significant treatment gap. Dental implants have emerged as the gold standard for tooth replacement due to their superior function, stability, and aesthetic outcome compared to conventional dentures. This case report discusses a 63-year-old female patient who presented with chewing difficulties and esthetic concerns due to the loss of mandibular teeth numbers 45 and 46. Clinical and radiographic examinations revealed adequate alveolar bone volume, a healthy periodontal condition, and no systemic contraindications despite a history of anti-cancer drug use more than 15 years prior. Two implants, with a diameter of 4.6 mm and a length of 10.5 mm, were placed in the mandibular premolar and molar regions, followed by the placement of healing abutments and porcelain-fused-to-metal crowns after osseointegration. Postoperative evaluations revealed excellent implant stability, improved masticatory function, and high aesthetic satisfaction, with a significant positive psychological impact. This case demonstrates the effectiveness of dental implants as a reliable rehabilitation option that enhances oral health and improves quality of life. had them replacedprovide a functional, stable, and aesthetically pleasing DOI : 10.54052/jhds.v5n2/163-176